Interoceptive conditioning with nicotine using extinction and re-extinction to assess stimulus similarity with bupropion - Charntikov, Sergios (2014)
Bupropion is an atypical antidepressant that increases long-term quit rates of tobacco smokers. A better understanding of the relation between nicotine and this first-line medication may provide insight into improving treatment. For all experiments, rats first had nicotine (0.4 mg base/kg) and saline session intermixed; intermittent access to sucrose only occurred on nicotine session. Nicotine in this protocol comes to differentially control “anticipatory” dipper entries. To more closely examine the overlap in the interoceptive stimulus effects of nicotine and bupropion, we assessed whether subsequent prolonged and repeated non-reinforced (extinction) sessions with the bupropion stimulus could weaken responding to nicotine (i.e., transfer of extinction). We also examined whether retraining the discrimination after initial extinction and then conducting extinction again (i.e., re-extinction) with bupropion would affect responding. We found that bupropion (20 and 30 mg/kg) fully substituted for the nicotine stimulus in repeated 20-min extinction sessions. The extent of substitution in extinction did not necessarily predict performance in the transfer test (e.g., nicotine responding unchanged after extinction with 20 mg/kg bupropion). Generalization of extinction back to nicotine was not seen with 20 mg/kg bupropion even after increasing the number of extinction session from 6 to 24. Finally, there was evidence that learning in the initial extinction phase was retained in the re-extinction phase for nicotine and bupropion. These findings indicate that learning involving the nicotine stimuli are complex and that assessment approach for stimulus similarity changes conclusions regarding substitution by bupropion. Further research will be needed to identify whether such differences may be related to different facets of nicotine dependence and/or its treatment.